A conceptual framework for assessing social and environmental impacts of belt and road initiative and just energy transition - Ge, Taoan (Frontiers in Sustainable Food Systems, 2022)
To address the social and environmental impacts of China's Belt and Road Initiative (BRI) and just energy transition, this research provides a conceptual framework to assess social and environmental impacts by selecting socioeconomic and environmental indicators through a literature review. The framework highlights that assessment indicators should include quantitative and qualitative dimensions. We also discussed the similarities and differences in foreign aid between developed countries and China's BRI, the relationship between the BRI, just energy transition and globalization, sustainable development goals (SDGs), and social-environmental resilience. This conceptual assessment framework and discussion provides stakeholders with an approach to contribute to mitigating the socio and environmental impacts of project development.